KONFLIK BATIN DALAM MITE PEREMPUAN INGKAR JANJI DALAM MASYARAKAT JAWA - Raharjo, Resdianto Permata (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Hasyim Asy'ari (Unhasy), 2016)
Majority of Indonesian have myths in every of their dwellings. Myth is the story talks about Gods, holy and sacred people that hereditary spread from the ancestors. The existence of myth is only known, believed, and influenced people who live in those villages, especially the elders who know the history of that myth. Myth has some influences for villagers living, such as rituals done by the villagers in some certain months for commemorating taboos. Internal conflict is reality life which is experienced by our society, both in real or story life. Conflict divided into two kinds, they are physical and internal conflict. Internal conflict refers to the anxious feeling because of the controversy between two desires, beliefs, and hopes. Internal conflict is more directed to the mental conflict inside the character. Internal conflict experienced in the story of unfaithful woman is the confusion of woman of rejecting ugly sacred man who has different belief in order he canceled his proposal. Internal conflict often presented to the readers in order to reject man not by physical or psychological efforts, but by the gentle and soft effort which is not damaging that man. Key Words: myth, internal conflict, physical conflict